EFEKTIVITAS KEGIATAN ECOPRINT BERBASIS KELOMPOK TERHADAP KEMAMPUAN KERJASAMA DITAMAN KANAK-KANAK YAYASAN AMALAN - Afriyeni, Anisa; Ismet, Syahrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Cooperation ability is an important aspect of social development in early childhood that needs to be stimulated through appropriate learning activities. However, learning activities in kindergarten are still dominated by individual tasks and teacher-centered approaches. This study aimed to determine the effectiveness of group-based ecoprint activities on children's cooperation ability at Taman Kanak-kanak Yayasan Amalan. This research used a quantitative approach with a quasi-experimental method and a pretest–posttest control group design. The research subjects consisted of 16 children divided into an experimental group and a control group. The instrument used was an observation sheet of children’s cooperation ability. Data were analyzed using the Mann–Whitney test and effect size calculation. The results showed a significant difference in cooperation ability between the experimental and control groups with a significance value of 0.001 (p < 0.05). The effect size calculation resulted in r = 0.847, which indicates a high effect category. Therefore, group-based ecoprint activities are effective in improving cooperation ability in early childhood.